Amelioration of motor and nonmotor symptoms in cortical cerebellar atrophy and multiple system atrophy-cerebellar type by inpatient rehabilitation: a retrospective study. Issue 2 (19th January 2021) - Sonoda, Yuma; Yamanaka, Yuya; Sawano, Shinichiro; Komada, Ryo; Kugo, Masato; Kitamura, Akihiro; Ogawa, Nobuhiro; Yamakawa, Isamu; Kim, Hyoh; Sanada, Mitsuru; Imai, Shinji; Urushitani, Makoto
Abstract : Supplemental Digital Content is available in the text. Abstract : Sporadic spinocerebellar degenerative diseases such as multiple system atrophy (cerebellar type) and cortical cerebellar atrophy typically present with cerebellar ataxia. Multiple system atrophy is characterized by ataxia, with parkinsonism, dysautonomia and neuropsychiatric symptoms, resulting in reduced quality of life. Effects of physical rehabilitation focused on motor symptoms with ataxia in nonmultiple system atrophy patients have been reported; however, without addressing concomitant nonmotor symptoms. Here, we examined the motor, nonmotor and quality of life effects of inpatient physical rehabilitation in 15 multiple systems atrophy and nine cortical cerebellar atrophy patients without dementia. Rehabilitation involved a 4-week hospitalization with physical, occupational and speech therapy. The following assessments were conducted at admission and discharge: the scale for the assessment and rating of ataxia for ataxia; Montreal cognitive assessment for cognition, hospital anxiety and depression scale for emotion and medical outcomes study short-form for health-related quality of life. Data were analyzed for statistical significance ( P < 0.05) using the Wilcoxon signed-rank test. In patients with multiple system atrophy, rehabilitation significantly improved ataxia, cognition with mild cognitive impairment (73.3%) and health-related quality of life; however, patients with depression (86.7%) showed no improvement in emotional health and quality of life. Similar effects on motor and nonmotor symptoms were observed in patients with cortical cerebellar atrophy. This suggests that inpatient rehabilitation could not only improve motor and nonmotor functions, but also the quality of life in patients with spinocerebellar degenerative disease.